Design of Micro Hydro Power Plant In Girimulyo Village - Rahmad Samosir; Medyawanti Pane; Lionardo Lionardo; Kimar Turnip (Universitas Sultan Ageng Tirtayasa, 2022)
The utilization of water as a natural resource from renewable energy for power generation is an alternative solution to replace the need for fossil fuels. In Girimulyo village, Ngargoyoso sub-district, there is a river that can be potential to become a Micro Hydro Power Plant. From field observations and calculations using the GPS (Global Positioning System) application, the water discharge Q = 0,2 m3/s. and the height of the waterfall H = 16,5 m. Based on the height and the existing water flow, it is determined that the turbine used is the Pelton turbine. From the calculation of the effective head of 15,81 m. With the water discharge used to rotate the Pelton turbine, the power obtained is 20,162 kW. From this power, it can be calculated that the shaft diameter is 38 mm. To make it easier to adjust the rotation between the generator and the Pelton turbine rotation, a flat belt type belt transmission with a width of 300 mm and a thickness of 9 mm is used while the maximum belt tension is 39 kg with a tangent angle between the pulley and the belt 7,180.